Evaluasi Program Pemberdayaan Ekonomi Masyarakat Pesisir Dalam Meningkatkan Kesejahteraan Nelayan (Studi Kasus Desa Sekunyit Kecamatan Kaur Selatan Kabupaten Kaur) - Purwanti, Tri (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This study aims to describe and analyze (1) the accuracy of the coastal community economic empowerment program in Sekunyit village, south Kaur district, Kaur district and (2) to analyze the inhibiting factors of the coastal community economic empowerment program in Sekunyit village, south Kaur district, Kaur district. This research is a qualitative case study research. The data sources in this study were the chairman of the maritime mina cooperative, the secretary of the maritime mina cooperative, and the treasurer of the maritime mina cooperative. The data collection method used in this research is the method of interview, observation, and documentation. Data processing is carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study are (1) the results of research regarding the evaluation of the economic empowerment program of coastal communities in order to improve the welfare of fishermen, (2) the achievement of the coastal community economic empowerment program (PEMP) in Sekunyit Village, (3) the accuracy of the achievement of the objectives of the coastal community economic empowerment program (PEMP). ) in Sekunyit Village, and (4) Inhibiting factors in Achieving the Objectives of the Economic Empowerment Program for Coastal Community (PEMP) in Sekunyit Village. The results of this study are useful for fishermen, schools, and other researchers..